PENERAPAN PERMAINAN LEMPAR TANGKAP BOLA BESAR TERHADAP MOTORIK KASAR SISWA AUTIS DI SLB - ARDIANSYA, ARI (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Student with autism spectrum disorder is a group of complex disorder, these disorder are characterized by difficulties in social interaction and behavior. This behavior recognize of the gross motor skills. For the student with autism spectrum disorder, the coordination of gross motor skill it can’t balance. One way to increase the gross motor skill for student with autism spectrum disorder there is juggling ball activity. This research is a pre experiment quantitative research by using pre-test and post test group design. Test is used to collect the data of gross motor skill before and after the Student with autism spectrum disorder are given the action. The action is given in 10 meeting. Each meeting consists of 2 x 35 minutes. The learning material given are juggling ball activity. The data analysis techniques are non parametric analysis and sign test. Results of data analysis using the formula sign test on the effect of implementation juggling ball activity of students with autism spectrum disorder are Ztabel Zh = 2.05 and = 1.96 at 5% significance level. It is proved that Ho is rejected and Ha accepted. So it can be conclude that “There is a significant effect of the effect of implementation juggling ball activity of students with autismspectrum disorder of SLB Dharma Wanita Sidoarjo”. Keyword : Juggling ball activity, gross motorskill